Piezochromic luminescence in all-inorganic core–shell InP/ZnS nanocrystals via pressure-modulated strain engineering. Issue 8 (1st June 2020) - Liu, Hao; Zhao, Xiaohui; Yang, Xinyi; Wang, Yixuan; Wu, Min; Jiang, Jutao; Wu, Guorong; Yuan, Kaijun; Sui, Laizhi; Zou, Bo
Abstract : The piezochromic luminescence and lattice mismatch with pressure in all-inorganic core–shell InP/ZnS nanocrystals. Abstract : Piezochromic materials alter their photoluminescent (PL) colors in response to the action of external force. Such materials have attracted much attention owing to their promising applications in pressure-sensing, optoelectronic memory and anticounterfeiting. However, almost all the reported piezochromic materials were limited to the organic matters or compounds containing organic components. Here we present piezochromic materials and pressure-induced optical response based on all-inorganic core/shell InP/ZnS nanocrystals (NCs). The InP/ZnS NCs exhibit noticeable PL color changes, shifting from orange (2.08 eV) to green (2.25 eV), with the PL intensity showing slight enhancement below an applied pressure of 2.5 GPa. Further compressing to fluorescence quenching produces an ultrabroad energy tenability range up to 400 meV. Structural and time-resolved PL lifetime studies, together with first-principle calculations, reveal the weakening of strain-induced defect states in the low pressure regime, which contributes to effective excition recombination, thus ensuring high fluorescence emission of InP/ZnS NCs. This work provides a promising strategy to prepare piezochromic materials of all-inorganic semiconductors, thereby greatly increasing the choice of materials for new applications.